2020
DOI: 10.1186/s40794-020-00118-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in adult patients with pre-existing chronic cardiac, respiratory and metabolic disease: a critical literature review with clinical recommendations

Abstract: Background: A high burden of severe disease and death from the coronavirus disease 2019 (COVID-19) has been consistently observed in older patients, especially those with pre-existing medical co-morbidities. The global pandemic lockdown has isolated many patients with chronic illnesses from their routine medical care. This narrative review article analyses the multitude of issues faced by individuals with underlying medical conditions during the COVID-19 pandemic. Methods: Sources for this publication were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
87
4
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 103 publications
6
87
4
12
Order By: Relevance
“…Almost all of the researches showed that there is a relation between age and developing critical condition in COVID-19 patients. The need for intensive care unit (ICU) admission is higher in older patients [ 41 ]. Many researchers indicated that patients older than 60–65 years old are at higher risk of mortality [ 13 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all of the researches showed that there is a relation between age and developing critical condition in COVID-19 patients. The need for intensive care unit (ICU) admission is higher in older patients [ 41 ]. Many researchers indicated that patients older than 60–65 years old are at higher risk of mortality [ 13 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-existing cardiovascular problems especially coronary heart disease put the patient at great risk of developing fatal form of novel coronavirus disease [ 41 ]. Lots of studies have mentioned cardiovascular diseases especially ischemic heart disease as a risk factor for mortality in COVID-19 patients [ 13 , 26 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The syndemic effects of SARS-COV-2 and cardiometabolic conditions are still being identified (Singer 2020). While relatively low death rates have been reported in populations with high rates of HIV, prompting speculation of the protective effects of ARV medication, other chronic conditions are clearly implicated in poor outcomes for COVID-19 (Flaherty et al 2020;Mahumud, Kamara, and Renzaho 2020). COVID-19, chronic conditions, and aging are linked in ways that stretch beyond clinical risk.…”
Section: Syndemics and Recursivitymentioning
confidence: 99%
“…A recently published review article discusses the challenges faced by patients with pre-existing chronic medical conditions, including CVD and diabetes, during the current global pandemic. 4 These vulnerable patients are more likely to develop severe COVID-19 requiring prolonged hospitalization and intensive care management. The clinical outcomes in obese COVID-19 patients are worse, and the fatality rate is higher in this group.…”
mentioning
confidence: 99%
“…The authors recommend that the weight gain associated with prolonged societal lockdown measures be addressed by concerted efforts to promote healthy eating and physical activity. 4 This is especially important in the obese population, many of whom will also have evidence of MAFLD.…”
mentioning
confidence: 99%